تفعيل دور الجامعات الجزائرية في نشر ثقافة ريادة الأعمال (في ضوء التجارب العالمية) - قسوم هديل ساسية; فزاعي أماني; خميس حليمة (university of eloued جامعة الوادي, 2025)
"تهدف هذه المذكرة إلى دراسة أهمية نشر ثقافة ريادة الأعمال في الجامعات ودور المبادرة الفردية والاعتماد على القدرات الذاتية في خلق فرص اقتصادية جديدة، حيث أصبح التفكير في إنشاء المشاريع الخاصة يتطلب مجموعة من المعارف والمهارات الأساسية. لا يمكن لأي شخص أن يخوض هذا المجال من دون إدراك طبيعة هذه الثقافة الحديثة، التي تركز على المبادرة والإبداع واستغلال الفرص المتاحة مهما كانت بسيطة. إن نجاح أي مشروع لا يتوقف فقط على توفر رأس المال، بل يرتبط بفهم عميق لعناصر النجاح، والإلمام بالمخاطر الممكنة وكيفية التعامل معها. في هذا السياق. تلعب المؤسسات الجامعية دورًا محوريًا في توجيه الطلبة وتعريفهم بكيفية اكتشاف أفكار جديدة وتحويلها إلى مشاريع فعلية.فهناك من يعتبر أن الجامعات يجب ألا تقتصر على التلقين النظري، بل عليها أن تواكب التطورات وتدمج برامج عملية تتيح للطلبة التفكير كرواد أعمال مستقبليين، خاصة وأن تجارب العديد من الدول أثبتت فاعلية هذه المقاربة. كما أن إشراك الطلبة في ورشات تكوينية، ملتقيات ومسابقات تطبيقية يعزز من قدراتهم على الابتكار وحل المشكلات التي تواجههم. من جهة أخرى، يساهم التعرف على تجارب عالمية ناجحة في تحفيز الشباب على التفكير بطريقة جديدة، بعيدة عن النمط التقليدي، تعتمد على الجرأة واتخاذ القرار، مع مراعاة أهمية التعلم من أخطاء وتجارب الآخرين. إذ أن البحث في أسباب نجاح بعض المشاريع وفشل أخرى يفتح آفاقًا أوسع لفهم سوق العمل وواقع الأعمال بشكل أدق. "This memorandum aims to examine the importance of spreading the culture of entrepreneurship in universities and the role of individual initiative and self-reliance in creating new economic opportunities. Considering the idea of establishing private projects has become a requirement for a set of basic knowledge and skills. No one can venture into this field without understanding the nature of this modern culture, which focuses on initiative, creativity, and exploiting available opportunities, no matter how simple. The success of any project does not depend solely on the availability of capital; it is also linked to a deep understanding of the elements of success, as well as familiarity with possible risks and how to deal with them. In this context. Universities play a pivotal role in guiding students and teaching them how to discover new ideas and transform them into practical projects. Some believe that universities should not be limited to theoretical indoctrination, but should keep pace with developments and integrate practical programs that enable students to think like future entrepreneurs, especially since the experiences of many countries have proven the effectiveness of this approach. Involving students in training workshops, forums, and applied competitions also enhances their ability to innovate and solve the problems they face. On the other hand, learning about successful global experiences helps motivate young people to think in a new way, away from traditional patterns, based on boldness and decision-making, while taking into account the importance of learning from the mistakes and experiences of others. Researching the reasons behind the success of some projects and the failure of others opens up broader horizons for a more accurate understanding of the job market and the business landscape."
Keywords: رياة الأعمال; التعليم الريادي; حاضنات الأعمال; ntrepreneurship; entrepreneurial education; Business incubators